Germinação de sementes in vitro e aclimatização de Euterpe edulis Martius - Baptista, Julcinara Oliveira (2022)
Euterpe edulis is propagated by mature seeds and, due to the hardness of the tegument and endosperm, it has slow ex vitro germination. However, immature seeds in in vitro cultivation can accelerate germination and produce normal axenic seedlings. The objective was to analyze the germination potential of embryos, seeds (immature and mature) in vitro and immature seeds ex vitro, and to select the explant of E. edulis with superior results for acclimatization. Three experiments were carried out: I: In vitro germination of zygotic embryos, immature seeds, intact and scarified mature seeds of E. edulis; II: In vitro germination of seeds and immature zygotic embryos of E. edulis in culture medium with GA3 and III: Acclimatization of seedlings from in vitro cultivation of immature seeds of E. edulis pre-germinated in different culture media and ex substrate vitro. We analyzed: germination, vigor and growth of seedlings in vitro and ex vitro, survival and growth of seedlings ex vitro. A completely randomized design was used, with three replications of 10 seeds in experiments I and II, and with six replications of five seeds in experiment III. The in vitro cultivation of immature seeds is advantageous in relation to zygotic embryos, mature seeds and ex vitro immature seeds. GA3, at concentrations of 0, 2, 4 and 8 mg L-1 for E. edulis seeds, did not induce seed germination. Immature seeds use nutritional reserves present in the endosperm for germination, because only through the solidification of water with agar is sufficient for the germination and initial growth of E. edulis, thus reducing production costs, discarding the need for a culture medium containing salts and nutrients.